THEORETICAL FUNDAMENTALS OF PUBLIC-PRIVATE PARTNERSHIP MANAGEMENT IN THE FIELD OF LOGISTICS OF SECURITY FORCES OF UKRAINE - Pysarevskyi, Serhii (Honor and Law, 2022)
It is established that in the context of the development of logistics of security forces, the experience of countries with market economies proves the relevance of the introduction of public-private partnership. Thus, at the present stage of development of a democratic Ukrainian society, the issue of public-private partnership management comes to the fore. A special place in the system of comprehensive support of the security forces of Ukraine is occupied by logistics. An adequate level of logistical support of the security forces in the event of crisis situations that threaten national security is the key to effective performance of assigned tasks. The purpose of the article is to study the theoretical tasks of public-private partnership management, as well as to substantiate the directions of this activity in the logistics of security forces of Ukraine. It is proved that today clear norms and rules of organization of public-private partnership in Ukraine have been established. However, the list of areas for public-private partnerships is too narrow. The legislator reserves the right to the public partner to apply public-private partnership in other areas of activity that provide socially significant services, except for economic activities that are allowed by law only to state enterprises, institutions and organizations. At the same time, public-private partnership is applied taking into account the peculiarities of the legal regime for certain objects and certain activities established by law. Therefore, the decision-making process on the application of public-private partnership mechanisms in the field of state security is too complecated and not devoid of corruption. Analysis of legal sources, research and practice of public-private partnership in Ukraine shows that this area is in its infancy. Currently, public-private partnerships are developed mainly in the public (municipal) sector, namely in housing and communal services, transport and medicine. At the same time, issues of development in the field of state security remain out of consideration. In this regard, we add that the implementation of effective mechanisms for responding to crises that threaten national security is impossible without modern logistics of security forces, including a set of measures for timely and complete recovery, receipt and stockpiling, provision of parts and units, accounting, maintaining and maintaining them in a state that ensures their timely readiness to use the tasks for their intended purpose. It is established that the public-private partnership in the field of logistics is currently in its infancy, and this area of ​​research has significant prospects. Therefore, the directions of further scientific research will be aimed at studying the current state of functioning of public-private partnership management mechanisms in the logistics of security forces of Ukraine and the EU and NATO countries.